TERAPI BEDAH PEMANJANGAN TUNGKAI VS TERAPI OBAT HORMONAL VOSORITIDE PADA PENDERITA AKONDROPLASIA : SYSTEMATIC REVIEW - Ameliana (2022)
Introduction: Achondroplasia is a bone growth disorder caused by mutations in the fibroblast growth factor-receptor-3 (FGFR-3) gene that causes the body to be short and disproportionate. This condition can be modified bylimb lengthening therapyother hand, various studies to date have shown that the C-natriuretic peptide (vosoritide) analogue is a promising therapy to increase the height of patients with achondroplasia. This review aims to determine the effectiveness and safety of both therapies. Methods: The literature search process was carried out using the SCOPUS, Pubmed, Science direct, Google Scholar, DOAJ databases. Results: In systematic review , based on 5 research literatures that have been selected using the PRISMA-P method, it shows that limb lengthening surgical therapy increases height with an average height gain that is almost as planned. In 4 literatures with vosoritide increase in growth rate was obtained up to 5.52 cm/year. The complication rate after limb lengthening surgery was higher than vosoritide with no complications found in the literature. Conclusion: Surgical treatment of limb lengthening increases the height of patients with achondroplasia more quickly but the complications caused are not lower than that of the hormonal drug vosoritide.